2017
DOI: 10.1007/s00729-017-0095-x
|View full text |Cite
|
Sign up to set email alerts
|

Ein neues Therapie-Konzept validiert die besonderen Bedürfnisse geflüchteter Kinder und Jugendlicher: START

Abstract: Zusammenfassung Die besondere Situation psychisch belasteter und geflüchteter Kinder und Jugendlicher erfordert neue Konzepte in der psychotherapeutischen Versorgung. Geflüchtete Kinder leiden häufig an psychischen und körperlichen Symptomen und sind durch traumatische Erlebnisse nachhaltig belastet. Das strukturierte und manualisierte Kurztherapiemanual "START" -Stress-Traumasymptoms-Arousal-Regulation-Treatment wurde im Rahmen der praktischen Arbeit mit unbegleiteten minderjährigen Flüchtlingen in Clearing-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The manualised Stress-Traumasymptoms-Arousal-Regulation-Treatment (START) programme was developed from clinical work with traumatised unaccompanied refugee minors in Germany to promote coping with traumatic distress and emotional irritability. [18][19][20] An uncontrolled pilot study in 22 traumatised refugee minors showed positive effects on emotion regulation, adaptive strategies, self-control, distress and good feasibility. 18 A subsequent study confirmed the positive effects on adaptive emotion regulation strategies.…”
Section: Study Objectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…The manualised Stress-Traumasymptoms-Arousal-Regulation-Treatment (START) programme was developed from clinical work with traumatised unaccompanied refugee minors in Germany to promote coping with traumatic distress and emotional irritability. [18][19][20] An uncontrolled pilot study in 22 traumatised refugee minors showed positive effects on emotion regulation, adaptive strategies, self-control, distress and good feasibility. 18 A subsequent study confirmed the positive effects on adaptive emotion regulation strategies.…”
Section: Study Objectivesmentioning
confidence: 99%
“…The original START programme was developed from clinical work with highly traumatised unaccompanied refugee minors of different countries of origin, who had recently arrived in Germany. [18][19][20] The adapted and extended version of the programme, that is evaluated in this RCT, was redesigned according to the participants' feedback of the pilot study groups, who were also traumatised refugee minors from different countries of origin. The public was not involved when designing the study.…”
Section: Patient and Public Involvementmentioning
confidence: 99%
See 2 more Smart Citations
“…START (Stress-Traumasymptoms-Arousal-Regulation Treatment) is a manualized short-term (5 weeks) treatment concept of stabilization and emotional regulation for extremely stressed adolescents and also for minor refugees. The intervention was constructed to offer adolescents, who are unmotivated or too unstable for Dialectical Behavior Therapy (DBT), reprocessing treatment, or long-term psychotherapy conditions, a first aid for crisis management and emotional stabilization ( 67 ). The program can be used for adolescents with diverse cultural backgrounds and repeatedly severe emotional distress, as a low-threshold training program to manage emotional dysregulation including skills to reduce self-harming and impulsive aggressive behavior.…”
Section: Introductionmentioning
confidence: 99%